2010
DOI: 10.2174/138920010791636149
|View full text |Cite
|
Sign up to set email alerts
|

Specific Hemosiderin Deposition in Spleen Induced by a Low Dose of Cisplatin: Altered Iron Metabolism and Its Implication as an Acute Hemosiderin Formation Model

Abstract: Cisplatin is one of the commonly-used chemotherapeutic drugs to efficiently treat malignant tumors in clinic, however, the adverse effects of cisplatin such as nephrotoxicity, neurotoxcity, and hemolytic uremic syndrome are often observed at its clinical doses (~60 mg/m 2 ), which limit its broader application. In earlier studies, little attention was paid to the subtle changes in the architecture of lymphatic organs after low doses of cisplatin treatment. This paper reviews current understanding of cisplatin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 41 publications
4
22
0
1
Order By: Relevance
“…The reduction of Hb concentration is due to erythrocyte damage induced by CP. These results are in agreement with those obtained by Wang et al who speculated that the splenic injury and hemosiderin deposition might be mainly due to abnormal erythrocyte damage induced by CP. Moreover, our data are consistent with those of Sachs and Lotem and Mazur et al who reported that CP toxicity, at therapeutic doses, to bone marrow cells was evident and probably CP can trigger apoptosis and affect cell cycle causing anemia and a decrease in TLC.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction of Hb concentration is due to erythrocyte damage induced by CP. These results are in agreement with those obtained by Wang et al who speculated that the splenic injury and hemosiderin deposition might be mainly due to abnormal erythrocyte damage induced by CP. Moreover, our data are consistent with those of Sachs and Lotem and Mazur et al who reported that CP toxicity, at therapeutic doses, to bone marrow cells was evident and probably CP can trigger apoptosis and affect cell cycle causing anemia and a decrease in TLC.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, brown staining was observed in the spleen from vorinostat or vorinostat and ABT-888 treated mice (panel 'a' in S7 Fig ). It has been noted before that accumulation of hemosiderin in the spleen of cisplatin-treated mice was associated with brown staining in H&E stained preparations [ 34 ]. Indeed Prussian blue staining revealed an increased level of splenic iron in vorinostat or vorinostat and ABT-888 treated mice (panel 'b' in S7 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…It is presumed that the liposomal formulation caused damage to erythrocytes, which accelerated their removal by macrophages in the spleen. [37] To assess acute toxicity, we performed hemograms and a blood biochemical analysis for the liver, renal, and muscle parameters in Balb/c mice after the administration of frequent dosages of aldox-NFP, aldox, and Doxil (2.5 mg kg −1 of drug content three times a week). None of the three treatments changed the number and morphology of the blood cells (Figure 8b).…”
Section: Resultsmentioning
confidence: 99%